Evening smartphone exposure impairs sleep quality and next-day performance in elite soccer players: A randomized controlled trial - Dridi, N.; Souissi, M. A.; Dridi, R.; Ceylan, H.; Bragazzi, N.; Salem, A.; Fekih, S.; Chtara, M.; Mkaouer, B.; Chtourou, H.; Dergaa, I.; Souissi, N.; et al. (Biology of Sport, 2026)
This study aimed to examine the effects of pre-bedtime smartphone use on sleep quality and athletic performance in soccer players while also investigating potential time-of-day variations. In this randomized controlled crossover trial, 16 male elite-level players were assigned to either use a smartphone for two hours prior to bedtime or read magazines (control), separated by a one-week washout period. Participants completed morning and afternoon performance tests (cognitive and physical assessments) and sleep quality measurements. Nocturnal smartphone use significantly impaired sleep quality, increasing sleepiness after days 3 and 5 (p < 0.01; d=5.74, d=5.72, respectively), decreasing total sleep time, increasing sleep onset latency, and reducing sleep efficiency (all p < 0.01; d=1, d=4.59). Cognitive performance initially showed improved afternoon results, although following five days of smartphone use, this pattern reversed with enhanced morning performance (p < 0.01; d=0.53, d=1.48). Simple and choice reaction times deteriorated significantly in afternoon sessions compared to both baseline and control conditions (p < 0.01; d=0.96-3.47). Physical performance tests revealed decreased jumping ability and slower reactive agility times following five nights of smartphone use, particularly in afternoon sessions (p < 0.01; d=0.85 0.91). Five consecutive nights of pre-bedtime smartphone use impaired sleep quality and both cognitive and physical performance in elite soccer players, with stronger effects in afternoon sessions. These findings emphasize the importance of implementing device-free periods prior to bedtime and potentially adjusting training schedules when evening screen exposure is unavoidable. Future research should explore countermeasures for managing evening device exposure in elite athletes.